Parent needs and family support service outcomes in a Canadian sample. (September 2013) - McConnell, David; Breitkreuz, Rhonda; Savage, Amber
Summary: Parent support needs and family support service (FSS) outcomes were investigated. A total of 923 parent participants were recruited through 20 community-based FSS providers in Alberta, Canada. Participants completed a survey, incorporating well validated child, parent and family outcome measures, a minimum of 8–12 weeks after utilizing their FSS. Findings: Overall, parent need satisfaction was high. However, low socio-economic status, English as a second language, parental disability or chronic health condition, and child disability or chronic health condition were associated with lower levels of parent need satisfaction. Higher levels of need satisfaction were linked to lower levels of parenting stress and more positive parent–child interactions. These, in turn, were linked to more positive family functioning and fewer child difficulties. Applications: Mediation analysis and qualitative findings suggest that family support services are making a positive difference by creating points of 'connection', including opportunities for informal learning and peer-support. We argue that the informal, 'social networking' role of family support services should be valued alongside evidence-based parenting training programs.